Evaluation of Carotid–Femoral Pulse Wave Velocity: Influence of Timing Algorithm and Heart Rate - Millasseau, Sandrine C.; Stewart, Andrew D.; Patel, Sundip J.; Redwood, Simon R.; Chowienczyk, Philip J. (Hypertension (Dallas, Tex. 1979), 2005)
Carotid–femoral pulse wave velocity (PWV), a measure of arterial stiffness, is determined from the time taken for the arterial pulse to propagate from the carotid to the femoral artery. Propagation time is measured variously from the foot of the waveform or point of maximum upslope. We investigated whether these methods give comparable values of PWV at rest, during β-adrenergic stimulation, and pacing-induced tachycardia. In subjects at rest (n=43), values obtained using the foot-to-foot method (SphygmoCor system) were 1.7±0.75 m/s (mean±SD) greater than those obtained using the maximum slope (Complior system) at a mean value of 12 m/s. Isoprotenerol (0.5 to 1.5 μg/min; n=10), and pacing (in subjects with permanent pacemakers; n=11) increased heart rate but had differential effects on systolic blood pressure and pulse pressure. The increase in heart rate produced by isoprotenerol (18±3 bpm) and pacing (40 bpm) was associated with an increase in PWV measured using both systems (increases of 0.7±0.2 m/s and 0.9±0.2 m/s for SphygmoCor and Complior, respectively, during isoprotenerol and increases of 2.1±0.5 m/s and 1.1±0.2 m/s for SphygmoCor and Complior, respectively, during pacing, each P<0.001). Reanalysis of waveforms recorded from the Complior system using the foot-to-foot method produced similar values of PWV to those obtained with the SphygmoCor, confirming that the difference between these systems was attributable to the timing algorithm rather than other aspects of signal acquisition. Carotid–femoral PWV is critically dependent on the method used to determine propagation time, but this does not account for variation of PWV with heart rate.